Psychometric evaluation and adaptation of the nursing informatics competency self-assessment tool - Arghavan Afra; Noorollah Tahery; Shima Seneysel Bachari; Masoud Torabpour Toroghi (حیات)
Background & Aim: Modern professional nursing necessitates the use of information technology to facilitate clinical decision-making and obtain optimal patient care outcomes. The aim of this study was to conduct a psychometric evaluation and adapt the Nursing Informatics Competency Self-Assessment tool for use in Iran. Methods & Materials: The present research employed a descriptive and methodological design. Initially, the original tool was translated into Persian following a standardized procedure. Subsequent assessments of face and content validity were conducted through expert reviews and the calculation of the content validity index. Reliability was evaluated using both Cronbach's alpha and test-retest methods, including the calculation of the intraclass correlation coefficient. Data analysis was conducted using confirmatory factor analysis on a convenience sample of 300 nursing students from the School of Nursing and Midwifery at Abadan University of Medical Sciences, utilizing SPSS version 22 and LISREL version 8.8. Results: The content validity index for all items exceeded the standard threshold of 0.79, indicating satisfactory validity scores for each item. The final version of the tool demonstrated acceptable reliability with a Cronbach's alpha coefficient of 0.898 and an intraclass correlation coefficient of 0.893. Confirmatory factor analysis indicated the fitness of a five-factor structure for the Persian version of the tool. Standardized factor loadings showed a good fit and satisfactory construct validity for the tool within the Iranian context. Conclusion: The Persian version of the Nursing Informatics Competency Self-Assessment Tool exhibits acceptable psychometric properties within the Iranian nursing population and is recommended for use as a credible instrument in nursing practice.